Apologétique et vulgarisation : les notes de lecture sur les « pamphlets » de Mgr de Ségur - Taro Nakajima (Flaubert: Revue Critique et Génétique)
The question is about how Flaubert’s reading notes on Mgr de Ségur’s “pamphlets”, taken in preparation of Bouvard et Pécuchet’s chapter IX (religion) and of the second volume, are used in the novel, especially for two types of discourses: the counter-revolutionary speech of M. de Faverges whose act of charity embodies Mgr de Ségur’s social Catholicism, and M. Jeufroy’s apologist’s speech, a condensed hodgepodge of common religious beliefs, which were probably inspired by his popularization works. The Catholic pamphleteer, attempting to eliminate anticlerical prejudices, becomes aware of the media’s influence on public opinion. While deriding his backward vision, Flaubert was interested in the way Mgr de Ségur’s booklets democratize modern religion, confronted with Protestant propaganda, by aiming at the working classes and popularizing his predecessors’ religious knowledge.